Math Is Fun Forum
  Discussion about math, puzzles, games and fun.   Useful symbols: ÷ × ½ √ ∞ ≠ ≤ ≥ ≈ ⇒ ± ∈ Δ θ ∴ ∑ ∫ • π ƒ -¹ ² ³ °

You are not logged in.

#1 2006-11-10 05:49:58

Neha
Member
Registered: 2006-10-11
Posts: 173

f(x)

let f(x) = x + 3  and g(x) = x^2 + 1
find: (f-g)(3)

i did>
   f(x) = x + 3
- g(x) = x^2 + 1
----------------------------
(f-g)(x) = x+3-(x^2+1)
            = x - x^2 - 2
(f-g)(3) = 3 - 3^2 - 2
            = 3 - 9 - 2
            = -8
is the answer
up


Live Love Life

Offline

#2 2006-11-10 05:54:54

luca-deltodesco
Member
Registered: 2006-05-05
Posts: 1,470

Re: f(x)

f-g -> x - x^2 + 2


The Beginning Of All Things To End.
The End Of All Things To Come.

Offline

#3 2006-11-10 06:21:26

Neha
Member
Registered: 2006-10-11
Posts: 173

Re: f(x)

why is it 2 instead of 1


Live Love Life

Offline

#4 2006-11-10 06:36:11

luca-deltodesco
Member
Registered: 2006-05-05
Posts: 1,470

Re: f(x)

you said f(x) = x+3, and g(x) = x^2 + 1, 3-1 = 2?


The Beginning Of All Things To End.
The End Of All Things To Come.

Offline

#5 2006-11-10 06:49:45

Neha
Member
Registered: 2006-10-11
Posts: 173

Re: f(x)

oh yeah i see that now
so my answer is now -4
correct


Live Love Life

Offline

Board footer

Powered by FluxBB